Total Glucosides of Paeony Ameliorate Pristane-Induced Lupus Nephritis by Inducing PD-1 ligands+ Macrophages via Activating IL-4/STAT6/PD-L2 Signaling - Liang, Chun-Ling; Jiang, Hongliang; Feng, Wenxuan; Liu, Huazhen; Han, Ling; Chen, Yuchao; Zhang, Qunfang; Zheng, Fang; Lu, Chuan-Jian; Dai, Zhenhua (Frontiers in Immunology, 2021)
Macrophages, a major subset of innate immune cells, are main infiltrating cells in the kidney in lupus nephritis. Macrophages with different phenotypes exert diverse or even opposite effects on the development of lupus nephritis. Substantial evidence has shown that macrophage M2 polarization is beneficial to individuals with chronic kidney disease. Further, it has been reported that PD-1 ligands (PD-Ls) contribute to M2 polarization of macrophages and their immunosuppressive effects. Total glucosides of paeony (TGP), originally extracted from Radix Paeoniae Alba, has been approved in China to treat some autoimmune diseases. Here, we investigated the potentially therapeutic effects of TGP on lupus nephritis in a pristane-induced murine model and explored the molecular mechanisms regulating macrophage phenotypes. We found that TGP treatment significantly improved renal function by decreasing the urinary protein and serum creatinine, reducing serum anti-ds-DNA level and ameliorating renal immunopathology. TGP increased the frequency of splenic and peritoneal F4/80+CD11b+CD206+ M2-like macrophages with no any significant effect on F4/80+CD11b+CD86+ M1-like macrophages. Immunofluorescence double-stainings of the renal tissue showed that TGP treatment increased the frequency of F4/80+Arg1+ subset while decreasing the percentage of F4/80+iNOS+ subset. Importantly, TGP treatment increased the percentage of both F4/80+CD11b+PD-L1+ and F4/80+CD11b+PD-L2+ subsets in spleen and peritoneal lavage fluid as well as the kidney. Furthermore, TGP augmented the expressions of CD206, PD-L2 and phosphorylated STAT6 in IL-4-treated Raw264.7 macrophages in vitro while its effects on PD-L2 were abolished by pretreatment of the cells with an inhibitor of STAT6, AS1517499. However, TGP treatment did not affect the expressions of STAT1 and PD-L1 in Raw264.7 macrophages treated with LPS/IFN-γ in vitro, indicating a possibly indirect effect of TGP on PD-L1 expression on macrophages in vivo. Thus, for the first time, we demonstrated that TGP may be a potent drug to treat lupus nephritis by inducing F4/80+CD11b+CD206+ and F4/80+CD11b+PD-L2+ macrophages through IL-4/STAT6/PD-L2 signaling pathway.